Novel endoscopic management for pancreatic pseudocyst with fistula to the common bile duct - Crinò, Stefano Francesco (World J Gastrointest Endosc, 2014)
Pancreatic pseudocyst formation is a well-known complication of pancreatitis. It represents about 75% of the cystic lesions of the pancreas and might be located within or surrounding the pancreatic tissue. Sixty percent of the occurrences resolve spontaneously and only persistent, symptomatic or complicated cysts need to be treated. Complications include infection, hemorrhage, gastric outlet obstruction, splenic infarction and rupture. The formation of fistulas to other viscera is rare and most commonly occurs within the stomach, duodenum or colon. We report a case of a patient with a pancreatic pseudocyst in communication with the common bile duct. There have been only few cases reported in the literature. We successfully managed our case by performing an endoscopic ultrasound-guided drainage of the pancreatic collection and a contemporaneous stenting of the common bile duct. Performed independently, both drainages are effective, safe and well-coded and the expertise on these procedures is widespread. By our knowledge this therapeutic approach was never reported in literature but we retain this is the most correct treatment for this very rare condition.